Lintasan Belajar Teorema Pythagoras dengan Pendekatan Pendidikan Matematika Realistik - Rangkuti, Ahmad Nizar; Siregar, Anwar Ibrahim (IAIN PADANGSIDIMPUAN, 2019)
The purpose of this study was to determine the validity and practicality of the learning trajectory through a realistic approach to the subject of the Pythagorean theorem in SMP Negeri 1 Hulu Sihapas. This research is a type of validation study design research that aims to develop local instruction theory (LIT) in collaboration with researchers and educators to improve the quality of learning. This research was conducted at SMP Negeri 1 Hulu Sihapas with product trial subjects in class VIII-A, totaling 26 students. Data collection instruments used were validation sheets, questionnaires and using validity and practicality analysis techniques. The results showed that: 1) the learning trajectory through a realistic approach is said to be valid with validity 85 of the analysis of 3 validators; and 2) the learning trajectory through a realistic approach is said to be practical with a value of 85.44 from the student response questionnaire. The learning trajectory generated in this study is in the form of activities undertaken by students to achieve learning objectives, namely to understand the Pythagorean theorem concept.